Why does the right to abortion continue to be discussed? - Irene COPPOLA (Revista Jurídica Portucalense, 2023)
The agile reflection, starting with a brief historical analysis, aims to demonstrate the absence of the right to abortion in Italy. The theme develops from the Law 194 of 1978 and the recent political-legal debate that aims to give women the possibility of a different choice.